The impact of gender inequality in education and employment on economic growth in developing Countries: Updates and extensions - Stephan Klasen; Francesca Lamanna (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2008)
Using cross-country and panel regressions, we investigate to what extent gender gaps in education and employment (proxied using gender gaps in labor force participation) reduce economic growth. Using most recent data and investigating a long time period (1960-2000), we update the results of previous studies on education gaps on growth and extend the analysis to employment gaps using panel data. We find that gender gaps in education and employment significantly reduce economic growth. The combined 'costs' of education and employment gaps in Middle East and North Africa and South Asia amount respectively to 0.9-1.7 and 0.1- 1.6 percentage point differences in growth compared to East Asia. Gender gaps in employment appear to have an increasing effect on economic growth differences between regions, with the Middle East and North Africa and South Asia suffering from slower growth in female employment.
Keywords: J7; J16; O4; 330; gender inequality; growth; education; employment; discrimination; Soziale Ungleichheit; Geschlechterdiskriminierung; Bildungswesen; Beschäftigung; Entwicklung; Wirtschaftswachstum; Entwicklungsländer